MEKANISME TOLERANSI DAN METODE SELEKSI TUMBUHAN YANG TAHAN TERHADAP CEKAM AN KEKERINGAN - Endang Gati Lestari (Research Center for Biology-Indonesian Institute of Sciences, 2006)
Water is the main parameter to determine whether the yield potential of a plant is obtained or not. Water deficit on the tissue causes the disruption of all chemical process in the plant metabolism resulted in the plant growth impediment.In order to acquire the drought tolerance variety, various efforts have been conducted. Among others, in addition to the selection and characterization of the available germ plasma along with its cross-breeding, the development of the drought tolerance plant is conducted through somaclonal varitype induction. In the cultivation of the drought tolerance plant, beside physiological mechanism and biochemistry related to the plant tolerant to drought, the procedure of the selective and optimal selection should be managed.Hence,the mastery of the optimum selection techniques, in a relatively short time, the new drought tolerance lines could be obtained.